EKONOMI MIKRO (Literatur Review) - Lale Ajeng Khalifatun Wardani; Aprilia Kusnadi Putri; Arini Ihwatun Nisa; Safira Maulinda; Alenia Juwita Dewi; Ulfatul Uyun; Dodik Muhaenim; Sopian Zaori (Nusadaya Journal of Multidiciplinary Studies, 2022)
Economics is a social science that involves a study in order to determine choices and consider the things that need to be done in that election. Economics is included in the branch of social science that focuses on the use of scarce or limited resources to meet human needs. While humans have various needs and are endless or unlimited. Regarding the existing problems, economics can look at problems from two angles, namely micro and macro. Microeconomics studies various activities of economic units, such as individuals, both individual persons, individual companies, or other individuals.